2008
DOI: 10.1002/polb.21494
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of some unimodal and bimodal linear low‐density polyethylenes at moderate and high supercooling

Abstract: Effect of molar mass distribution (MMD) and composition distribution (CD) on crystallization behavior of linear low-density polyethylene materials at moderate and high supercooling was studied using differential scanning calorimetry, hotstage polarized light microscopy, small-angle light scattering, and chip nanocalorimetry methods. A set of uni-and bimodal materials having small variation in average molar mass, density, and melt flow rate, but large differences in MMD and CD, was investigated. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…On the other hand, Zhang et al showed via molecular dynamics simulations that the behavior of the simulated blend was influenced by the total branch content of the system, which in view of the results mentioned above co‐crystallize, as well as by the actual branch content of the branched fraction. Proofs of this behavior were shown by Tian et al, by Hubert et al, and Krumme et al Krishnaswamy et al in particular showed how the introduction of SCB in the longest chains favors the formation of tie chains.…”
Section: Polymer‐based Crystallinity Modificationsmentioning
confidence: 85%
“…On the other hand, Zhang et al showed via molecular dynamics simulations that the behavior of the simulated blend was influenced by the total branch content of the system, which in view of the results mentioned above co‐crystallize, as well as by the actual branch content of the branched fraction. Proofs of this behavior were shown by Tian et al, by Hubert et al, and Krumme et al Krishnaswamy et al in particular showed how the introduction of SCB in the longest chains favors the formation of tie chains.…”
Section: Polymer‐based Crystallinity Modificationsmentioning
confidence: 85%
“…The reorganization kinetics in PET and iPS was studied in combination with conventional DSC at scanning rates Brought to you by | Stockholms Universitet Authenticated Download Date | 7/7/15 5:06 AM covering 8 orders of magnitude [69][70][71]. Isothermal and non-isothermal crystallization and the formation of different crystal polymorphs were analyzed in a wide range of temperatures and scanning rates applying DSC and the fast scanning setup in PE, iPP and PVDF [54,[72][73][74][75][76][77][78][79]. The complex behavior in the temperature range between glass transition and melting temperature was investigated in PBT [80].…”
Section: Fast Scanning Calorimetric Techniquesmentioning
confidence: 99%
“…The use of Ziegler-Natta (ZN) type catalysts when synthesizing LLDPEs makes them heterogeneous both in intermolecular and intramolecular terms [1], i.e. compared to materials synthesized by single-site catalysts, the ZN materials have a broad ethylene sequence length (ESL) distribution with considerable quantities of long sequences [1,2,3]. If unimodal LLDPEs are traditionally produced by a single reactor-catalyst system then bimodal polymer materials can be produced, besides using dual catalyst systems in a single reactor [4], in two cascaded reactors at different reaction conditions and feeds [5], which is comparable to blending two polymers of a different structure, resulting in a broad molar mass distribution (MMD).…”
Section: Introductionmentioning
confidence: 99%